Contrast Agents: Magnetically Decorated Multiwalled Carbon Nanotubes as Dual MRI and SPECT Contrast Agents (Adv. Funct. Mater. 13/2014). (April 2014) - Wang, Julie Tzu‐Wen; Cabana, Laura; Bourgognon, Maxime; Kafa, Houmam; Protti, Andrea; Venner, Kerrie; Shah, Ajay M.; Sosabowski, Jane K.; Mather, Stephen J.; Roig, Anna; Ke, Xiaoxing; Van Tendeloo, Gustaaf; et al.
<x xml:space="preserve">Abstract</x> Multiwalled carbon nanotubes (CNTs) are cylinder‐structured nanomaterials composed of rolled‐up graphene sheets. G. Tobias, K. T. Al‐Jamal, and co‐workers carefully decorated CNTs with superparamagnetic iron oxide nanoparticles capable of magnetic resonance imaging, and subsequently tagged them with a nuclear imaging probe via a bisphosphonate linker. The hybrid successfully bridges two clinically important imaging techniques—magnetic resonance and nuclear imaging—thus combining the high resolution and sensitivity offered by each technique. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>